The Urgency of Administrative Reform in E-Government-Based Recruitment of General Elections Commission Members in Bali Province - Widhiasthini, Ni Wayan; Yanti, Ni Kadek Winda; Subawa, Nyoman Sri; Utami, Made Srinitha Millinia (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2024)
This study aims to explore the role of information technology, particularly the application of e-government, in the recruitment process for General Elections Commission (KPU) members, focusing on administrative reform in Bali. It emphasizes the optimization of administrative reform through an e-government-based recruitment system. Utilizing a qualitative research framework, this study employed a descriptive approach with a post-positivist perspective. Data were collected through interviews, observations, and document analysis, followed by systematic stages of data reduction, presentation, and conclusion drawing. Both qualitative and quantitative data were collected from primary and secondary sources and validated through source triangulation and determination. Informants were purposively selected based on several criteria, including expertise, involvement, and familiarity with the Information System for KPU Members and Adhoc Bodies (SIAKBA). Bali was chosen as the study site due to its status as a democratic benchmark in Indonesia and a globally recognized tourism appeal despite low public participation in elections. The findings indicate that SIAKBA supports administrative reform across five dimensions: information, transparency, participation, collaboration, and information technology in the provincial-level recruitment process. The study concludes that the administrative reform implemented through the recruitment system at KPU of Bali aligns with the principles of e-information, e-commerce, and e-democracy. This study recommends that e-democracy be further optimized in recruitment processes, considering the growing interest of individuals in joining KPU and contributing as democratic actors. Theoretical findings suggest that e-government has emerged as a standard for achieving administrative transformation.